Research on sustainable development of tourist attractions in Chongqing under the background of epidemic normalization. A case study of Wulong 5A Karst travelling site - Li, Weichen; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
Since the outbreak of COVID-19 in early 2020, the epidemic has gradually become normalized. This has affected all sectors in China, especially tourism, which has been hit hard. Many travelling sites have to close, making it difficult to make a living. This paper studies Wulong Karst scenic spot by case study method and SWOT analysis method, and puts forward suggestions and countermeasures to the existing problems of this scenic spot, so that Wulong Karst scenic spot, as a world natural heritage, can better maintain sustainable development under the background of the epidemic.